SPATIO-TEMPORAL INFORMATION SYSTEM ANALYSIS OF REVENUE ALLOCATION IN NIGERIA (1999-2008) - Olubusoye E. Olusanya; Oyedotun Temitope D. Timothy (European Scientific Journal, ESJ, 2014)
The bulk of the federally allocated revenue derived from revenue accruing to the Federal Government of Nigeria is shared with the other two tiers of government under a revenue allocation system (RAS) using different formulas at different times. The sharing principle has remained a contentious issue to date. This paper presents a spatio-temporal analysis of three items of revenue allocation namely, statutory, excess crude oil, value added tax and 13% share of derivation shared among the three tiers between May 1999 – December 2008. A comparative analysis was conducted among 6 geo-political zones, 36 states and 774 local government areas of the country. The result shows that when allocations from the four items of revenue are combined, the South-South zone leads with incredible margin, thus raising questions about the legitimacy of agitations from this zone.